2018
DOI: 10.1039/c8ob00187a
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective reduction of the tricarbonyl moiety in bicyclic tetramates giving pyroglutamates

Abstract: The reduction of C(6)-acyl bicyclic tetramic acids has been achieved with complete diastereoselectivity via catalytic hydrogenation using PtO2. The resulting pyroglutamates had potent antibacterial and anticancer properties and will allow the preparation of simple mimics of pyroglutamate-containing natural products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…27 Moreover, we have also shown that reduction of the C (7) ketone group is possible in high diastereoselectivity after hydrogenation with PtO 2 followed by elimination, leading to alkenes 3. 28 Therefore, key to the synthesis of closer mimics of the natural products in Figure 1 is C(6)-side chain manipulation allowing the introduction of the dienoyl functionality, and we report here work which demonstrates that such side-chain manipulation using a general approach based upon organometallic substitution is feasible on densely functional tetramate skeletons and that the derived products may exhibit antibacterial activity. ■ RESULTS AND DISCUSSION Preparation of Dienoyl Tetramates.…”
Section: ■ Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…27 Moreover, we have also shown that reduction of the C (7) ketone group is possible in high diastereoselectivity after hydrogenation with PtO 2 followed by elimination, leading to alkenes 3. 28 Therefore, key to the synthesis of closer mimics of the natural products in Figure 1 is C(6)-side chain manipulation allowing the introduction of the dienoyl functionality, and we report here work which demonstrates that such side-chain manipulation using a general approach based upon organometallic substitution is feasible on densely functional tetramate skeletons and that the derived products may exhibit antibacterial activity. ■ RESULTS AND DISCUSSION Preparation of Dienoyl Tetramates.…”
Section: ■ Introductionmentioning
confidence: 81%
“…The crude product was purified by flash column chromatography (10% EtOAc in petroleum ether) to give a 1:1 unseparable diastereomeric mixture of epoxide 24 (43 mg, 0.089 mmol, 64%) as a light yellow oil: R f (10% EtOAc in petroleum ether) 0.19; ν max /cm −1 2960 (C−H), 2931 (C− H), 1754 (CO), 1711 (CO), 1671 (CO), 1618 (CC), 1585 (CC); δ H (500 MHz, CDCl 3 , 1:1 mixture of diastereomers A and B) 0.88 (6H, t, J 6.8, C(11′)H 3 A + B), 0.91 (9H, s, C(CH 3 ) 3 A), 0.91 (9H, s, C(CH 3 ) 3 B), 1.09 (3H, d, J 6.0, i Pr A), 1.09 (3H, d, J 6.0, i Pr B), 1.25−1.37 (12H, m, C(8′−10′)H 2 A + B), 1.31 (3H, d, J 6.0, i Pr A), 1.32 (3H, d, J 6.0, i Pr B), 1. 40 5-Allyl-2-(triisopropylsilyl)oxazole (28). CuCN (495 mg, 5.52 mmol) and LiCl (485 mg, 11.4 mmol) were stirred at 130 °C under vacuum for 5 h. After the mixture was cooled to room temperature, anhydrous THF (10 mL) was added, and stirring was continued for further 30 min.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to β-lactams, the amide bond geometry of structurally characterized amides embedded in a fused five-membered ring system (Figures –) , can be characterized as N-pyramidalized (average χ N of 45.9°) with minimal twist (average τ of 11.7°). As expected, the average values of N-pyramidalization and twist are slightly lower as compared to β-lactams ...…”
Section: Cyclic Amides: N-pyramidalization 40–60°mentioning
confidence: 99%
“…123 The protected Weinreb amide 76a also provided access to pyroglutamate 78a by catalytic reduction. 124 With the successful conversion of tetramates into pyroglutamates by catalytic reduction, it became of interest to extend this approach, and we wondered if transitionmetal-mediated couplings on a suitable derivative might be feasible. Thus, conversion of 59a-d into mesylates 79a-d was effected, and Pd(0) couplings provided access to the substituted systems 80a-d; these could be readily reduced under mild hydrogenation conditions, giving diastereoselective access to pyroglutamates 81a-c, and bringing us full circle back to where our journey had started, with the de-velopment of approaches to functionalised pyroglutamates (Scheme 11).…”
Section: Short Review Syn Thesismentioning
confidence: 99%